THE USE OF MIND MAP IN MASTERING VOCABULARY THROUGH PICTURE AT THE SEVENTH GRADE OF SMP NEGERI 4 LIBURENG - Harmilawati Harmilawati (JLE: Journal of Literate of English Education Study Program, 2020)
The aims of this research is to find out whether or not mind map through picture canimproves students’ vocabulary mastery. To analyze the data, a pre-experimentaldescriptive quantitative design was employed. It involves seventh graders class in aschool at Libureng in academic year 2010/2011 with number of students, 30 students(15 males and 15 females). In collecting the data, the present study used pre-test andpost-test as the instrument then calculated them by using normality, validity, reliability,gain test and t-test. The findings show that the value of t-obtained was 11,82 and thevalue of t-table at significance level of 5% was 2,045 with the degree of freedom(df=29). The result of t-obtained (11,82) indicates that H0 is rejected and consequentlythe H1 is accepted. It means that the use of mind map method can improves students’vocabulary mastery. The students claim that this method offers interesting learning,challenge creativity, and serves new simple method to memorize some vocabularies. So,it is recommended for further researcher to conduct a research for other skills andother methods.